Repeatability of wide-field choroidal thickness measurements using enhanced-depth imaging optical coherence tomography - Hoseini-yazdi, Hosein; Vincent, Stephen J; Collins, Michael J; Read, Scott A; Alonso-caneiro, David (Clinical and experimental optometry, 2019)
To examine the repeatability of choroidal thickness measurements across a 55° field, in a sample of healthy young adults using wide-field enhanced-depth imaging optical coherence tomography. High-resolution wide-field volumetric enhanced-depth imaging scans were obtained from the right eye of 27 adults (mean age 27 ± 5 years) during two sessions, separated by 19 ± 15 days, using the follow-up feature of the Spectralis instrument, while controlling for confounding factors known to influence choroidal thickness. Semi-automatic segmentation of the choroidal boundaries was corrected by a single masked observer. This process was repeated on images from the first session of 12 randomly selected subjects, allowing the intersession (n = 27) and intraobserver (n = 12) co-efficients of repeatability for regional measures of choroidal thickness to be calculated. The observer-related variability in choroidal thickness was highest at the fovea (intraobserver co-efficient of repeatability [95% confidence interval], 13 [7-19] μm, p < 0.001), then reduced gradually toward the perifovea (2 [1-4] μm, p < 0.001), and plateaued in the near-peripheral (2 [1-3] μm) and peripheral (4 [2-6] μm) regions. The intersession variability improved significantly from the fovea (intersession co-efficient of repeatability [95% confidence interval], 27 [16-38] μm, p < 0.01) and parafovea (25 [15-36] μm, p < 0.02) toward the periphery (16 [10-23] μm). Wide-field choroidal thickness measurements using enhanced-depth imaging optical coherence tomography are highly repeatable in the macular region, and improve in precision in more peripheral regions in healthy young adults. A change of up to 38 and 28 μm is required to distinguish true clinical change from measurement variability in individual measurements of macular and extra-macular choroidal thickness, respectively.